Identifikasi Hoax pada Media Sosial dengan Pendekatan Machine Learning - Laksana Utama, Putu Kussa (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
The Hoax propagation on social media is a problem that has to be solved. The main problem with the propagation of hoaxes on social media is that they can go viral very quickly. There have been various approaches developed to identify Hoax in the earlier stage. This study is conducted in order to analyze the various approaches that have been developed by many researchers in Hoax's identification domain. The result of literature study from various scientific papers shows that Hoax identification on social media is better if performed automatically using Machine Learning. On the several datasets, they have successfully obtain best-case accuracy of 75% -96%.